Logistical Factors in Determjning the Sigillficance of Operation of the port of Rijeka - Kovačević, Dražen; Baričević, Hrvoje; Macura, Arijana (Promet - Traffic&Transportation, 2012)
The basic logistical advantage of the Rijeka traffic routeand port as its starting and end point is the geographical positionat the crossroads of the Adriatic- Central Europe transportroute, in the region where the Adriatic Sea enters deepest intothe European mainland.Apart from the favourable geographic position, the advantageof the port of Rijeka is its natural characteristic- sufficientdepth.The port of Rijeka belongs to the categ01y of'old'p011S witha long tradition and rich experience in its operation.